Probabilistic Infrastructure Failure Cost Analysis Integrating with Equity Cost Using the Reliability Analysis - Yasaman Norouzi; Seyed Hooman Ghasemi; Mohammad Jalayer (Computational Engineering and Physical Modeling)
Quantifying infrastructure failure costs is pivotal for fostering target reliability and advancing equitable outcomes. Direct and indirect failure cost analyses must account for equity parameters such as fatalities, accessibility, and the fair distribution of benefits and burdens, particularly in transportation policies facing disruption. This paper critically examines existing methods for assessing the indirect costs of infrastructure failure through an equity lens. It synthesizes these approaches into a unified framework of probabilistic failure cost indices. Addressing notable gaps and disparities in the literature, we introduce a novel probabilistic-based metric designed to measure infrastructural costs comprehensively. Our main contribution is developing an inclusive framework that employs a detailed probabilistic formulation, capturing the interactions among key equity agents, including communities, hazards, infrastructure elements, and regulatory bodies. This formulation explicitly considers factors such as accessibility and exposure. Furthermore, we explore Agent-Based Functionality Modeling to achieve a multidimensional understanding of infrastructure failure costs. By analyzing past case studies and user data, we demonstrate the disproportionate impacts of infrastructure disruptions on marginalized communities. We also propose a new set of limit state functions (LSFs) tailored to operational variables, enabling the quantification of infrastructure operational levels by incorporating utility functionality assessments and failure-associated costs. Our framework dynamically integrates system functionality and utility uncertainties, providing a comprehensive and equitable tool for evaluating, predicting, and enhancing infrastructural resilience.